Event motivational factors influence towards visitor attendance at International Kites Festival, Pasir Gudang Johor / Noor Syuadah Ismail, Nurfarrahin Syazwanie Ramlee and Siti Norhidayah Md Yusof - Ismail, Noor Syuadah; Ramlee, Nurfarrahin Syazwanie; Md Yusof, Siti Norhidayah (2015)
The purpose of this study is to understanding the event motivational factors that affects visitors’ decision making to attend International Kites Festival at Pasir Gudang Johor. Moreover, the decision of the tourists will then leads towards their action to attend the festival. The respondents were visitors who attend the International Kite Festival. The researchers gather the data using questionnaires that distributed to the respondents at that festival which held at Bukit Layang-layang Johor. This study used descriptive research design with quantitative approach. A total of 50 complete questionnaires were used in this research. On top of that, data collected in this study was analysed by using frequency, reliability analysis, descriptive analysis and also regression analysis in order to achieve research objectives. The visitors believed that the escape and event novelty factors were the strongest influences that attract them as well as in making the decision to attend the festival.